2013
DOI: 10.1007/s00277-013-1794-1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the use of long-term central venous catheter in children with hemato-oncological disorders. On behalf of supportive therapy working group of Italian Association of Pediatric Hematology and Oncology (AIEOP)

Abstract: In the last 30 years, the use of long-term central venous catheters (CVC) is increased especially for children with hemato-oncological disorders. However, the use of CVC is associated to complications, as mechanical accidents, thrombosis, and infections that can determine a prolongation of hospital stay, an increase of costs, and sometimes life-threatening conditions that require urgent systemic treatment or CVC removal. CVC removal may be troublesome especially in neonates, infants, or any other "highly neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…In the prevention of CLABSIs, the use of lock solutions containing taurolidine, ethanol or citrate appears to be promising; however, further research on this subject is needed and strongly recommended [11,29,[32][33][34][35]. Patients diagnosed with hematooncologic malignancies were more at risk for CVAD-related complications in general; this might be because of more frequent CVAD-manipulation in this patient group [1,7,9]. The insertion of an HB-CVAD appeared to be a significant risk factor for CVAD-related complications in general, dislocations and CLABSIs in particular.…”
Section: Microorganismsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the prevention of CLABSIs, the use of lock solutions containing taurolidine, ethanol or citrate appears to be promising; however, further research on this subject is needed and strongly recommended [11,29,[32][33][34][35]. Patients diagnosed with hematooncologic malignancies were more at risk for CVAD-related complications in general; this might be because of more frequent CVAD-manipulation in this patient group [1,7,9]. The insertion of an HB-CVAD appeared to be a significant risk factor for CVAD-related complications in general, dislocations and CLABSIs in particular.…”
Section: Microorganismsmentioning
confidence: 95%
“…The appropriate CVADs were chosen by health care professionals depending on the risks, frequency of use, quality of the veins, and duration/type of treatment [1][2][3]. Peripherally inserted central catheters (PICCs), nontunneled (NT) CVADs, HB-CVADs and TIVAPs were inserted.…”
Section: Cvad Insertion and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…A power calculation with our current results considering the incidence density of all BSIs revealed that we would have had to include more than 400 consecutive patients to reach a power of 80% (two-sided chi square test with a p<.05 significance level). Multicentre studies dealing with issues of supportive care are difficult to design, mainly because of the missing conformity in CVAD maintenance standards between centres [ 19 ], [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although such a large number of included patients may be generated in multicenter studies (e.g., involving all interested GPOH pediatric oncology centers), an identical prevention bundle must be defined for all participating POCs [ 19 ], [ 149 ].…”
Section: Preventive Bundle Studies To Prevent Cr-bsimentioning
confidence: 99%